Converting a Geriatrics Clinic to Virtual Visits during COVID-19: A Case Study - Sowmya Iyer; Priyanka Mehta; Joanne Weith; Dat Hoang-Gia; Janet Moore; Chalise Carlson; Philip Choe; Erin Sakai; Christine Gould (SAGE Publishing, 2021)
Background: To characterize the experience of converting a geriatrics clinic to telehealth visits in early stages of a pandemic. Design: An organizational case study with mixed methods evaluation from the first 8 weeks of converting a geriatrics clinic from in-person visits to video and telephone visits. Setting: Veteran's Health Administration in Northern California Participants Community-dwelling older Veterans receiving care at VA Palo Alto Geriatrics clinic. Veterans had a mean age of 85.7 (SD = 6.8) and 72.1% had cognitive impairment. Intervention: Veterans with face-to-face appointments were converted to video or telephone visits to mitigate exposure to community spread of COVID-19. Measurements: Thirty-two patient evaluations and 80 clinician feedback evaluations were completed. This provided information on satisfaction, care access during pandemic, and travel and time savings. Results: Of the 62 scheduled appointments, 43 virtual visits (69.4%) were conducted. Twenty-six (60.5%) visits were conducted via video, 17 (39.5%) by telephone. Virtual visits saved patients an average of 118.6 minutes each. Patients and providers had similar, positive perceptions about telehealth to in-person visit comparison, limiting exposure, and visit satisfaction. After the telehealth appointment, patients indicated greater comfort with using virtual visits in the future. Thirty-one evaluations included comments for qualitative analysis. We identified 3 main themes of technology set-up and usability, satisfaction with visit, and clinical assessment and communication. Conclusion: During a pandemic that has limited the ability to safely conduct inperson services, virtual formats offer a feasible and acceptable alternative for clinically-complex older patients. Despite potential barriers and additional effort required for telehealth visits, patients expressed willingness to utilize this format. Patients and providers reported high satisfaction, particularly with the ability to access care similar to in-person while staying safe. Investing in telehealth services during a pandemic ensures that vulnerable older patients can access care while maintaining social distancing, an important safety measure.